The Influence of Investment Decisions and Dividend Policy on Corporate Values - Sukarno (Journal of Research in Business, Economics, and Education, 2020)
The phenomenon of car sales has declined based on sales reports because Indonesia is recovering from a weakening Rupiah exchange rate that has continued to depreciate since 2018. In general, the automotive and component business segment recorded a 1% decrease in Net Revenue in 2018, as was the case with Profit The automotive segment net also fell by 14% from Rp. 9.8 trillion in 2018. This research was conducted to find out how much investment decisions and dividend policy on the value of the company in the automotive and component sub manufacturing companies on the Indonesia Stock Exchange. the data collection method uses secondary data in the form of financial statements from the Indonesia Stock Exchange. The data obtained were then processed using the multiple regression method with SPSS software version 23.00. The results showed that investment decisions partially had no effect on firm value. Dividend policy partially has a significant effect on firm value. Simultaneously there is a significant influence of the independent variable Investment Decision and Dividend Policy together on the Firm Value dependent variable.